Education on Corpse Care Using the Demonstration Method: An Effort to Improve Understanding of Islamic Sharia - Moch. Hasan Sidqi; Hasmi Nur Bayhaqi; Amir Bandar Abdul Majid; Iszanul Dani Nurdiansyah; M. Yusron Maulana El-Yunusi; Didit Darmawan (Institut Agama Islam Al-Fatimah Bojonegoro, 2024)
Caring for a corpse is an important practice that must be learned, as it is considered obligatory in Islam when no one else is available to perform it. This community service project aims to enhance understanding of both the theoretical and practical aspects of corpse care among students at Nurul Mushofa Islamic Boarding School in Tambak Lekok Village and Darun Najah MTs in Tampung Lekok Village, Pasuruan. The project was based on research conducted using the Participatory Action Research method. The results indicate that students at Nurul Mushofa Islamic Boarding School and MTs Darun Najah have significantly improved their knowledge and skills in both the theoretical and practical aspects of corpse care